Parental correlates of body weight status among high school students in Tehran - Jalali-Farahani, Sara; Chin, Yit Siew; Mohd Taib, Mohd Nasir; Amiri, Parisa (Kowsar Publishing Company, 2017)
This study aimed to determine the parental correlates of body weight status among adolescents in Tehran. The participants were 465 high school students and their parents who resided in Tehran. Body weight and height of the students were measured, and body mass index (BMI)-for-age and body weight status of the students were determined according to the world health organization growth reference (2007). Parents of the students completed a self-administered questionnaire including socio-demographic information, self-reported parental body weight and height, and parental perception of student’s body weight status. About half of the parents had an incorrect perception about body weight status of their children with higher rates of underestimation than overestimation. The percentage of parents who correctly perceived body weight status of the students decreased from 100.0% in severe thinness group to 14.0% in obese group. There were no significant associations between marital status, occupation, and education of parents and BMI-for-age of the students. While, both BMI of mother and BMI of father were significantly associated with students’ BMI-for-age (r = 0.29 and r = 0.27, respectively; P < 0.05). A great number of parents had incorrect perception regarding body weight status of their offspring; this was true specifically for parents of overweight and obese students. Both parental BMI and parental perception regarding students’ body weight status were associated with students’ BMI-for-age, indicating the need for parental involvement in weight management programs targeting adolescents.